Design and Implementation of an Aquarium Automation System Using a NodeMCU - Riko Reynaldi; Dani Hamdani (International Journal of Industrial Research and Applied Engineering, 2021)
Ornamental fish enthusiasts sometimes busy with other matters that take a long time so they do not have time to care for their pet fish. Therefore it is needed automation in maintaining fish in the aquarium. This study aims to make it easier to maintain ornamental fish in the aquarium by automate feeding activities, replacing water, and adjusting water temperatures. This automation uses the prototype method so that it is easy to improve continuously, data collection is done by collecting several articles related to the title taken by the author. NodeMCU is used as a temperature sensor data reader, pH, Ultrasonic and servo data receiver, relay to turn on the valve, pump, heater, fan. The results of the data will be sent wirelessly to smartphones via the Blynk application. The results of this study are a tool that can feed according to a predetermined schedule, replacing water according to the acidity of the water's pH, and adjusting the temperature to its natural habitat. Thus this automation tool will be useful for fans who are busy with their work, especially those who often go out of town in days.